Future and development direction (21-35) of M&S for building up to the hyper-army in Republic of Korea Army: Focusing on fostering high-tech armed forces - Won, Kyoungchan; Kim, Yongpil; Kim, Minsuk; Ha, Taegyun; Lee, Yongyeon; Lee, Hojun (Journal of Advances in Military Studies, 2021)
This study presents the direction of modeling and simulation (M&S) development, which is essential for high-tech armed forces, focusing on the Vision 2030 in Republic of Korea Army. In particular, in preparation for the Fourth Industrial Revolution, the army is doing its best to transform itself with cutting-edge science and technology. It is preparing for future warfare by promoting artificial intelligence (AI), a dronebot combat system, the warrior platform, and Army-Tiger 4.0 to increase the mobility, intelligence, and networking of infantry units. M&S is vital for accomplishing this advanced science and technology. In other words, it is an essential element of effective defense management, such as improving defense capabilities, enhancing military power, strengthening combat readiness posture, and training for future science. In particular, M&S is the best solution to overcome the difficult conditions of a limited budget and lack of resources by using more creative thinking methods along with cutting-edge technologies, such as AI, big data, virtual reality, and the Internet of things (IoT). The Republic of Korea Army recognizes its importance and intends to introduce and implement the 21-35 Army M&S development direction to present the vision and direction of the Army M&S for advanced science and technology force and to develop it continuously.